2012
DOI: 10.1186/1752-1947-6-300
|View full text |Cite
|
Sign up to set email alerts
|

Orbital intravascular papillary endothelial hyperplasia in a Nigerian child: a case report and review of the literature

Abstract: IntroductionIntravascular papillary endothelial hyperplasia is a reactive proliferative lesion of endothelial cells in blood vessels. It typically presents as a painless, reddish purple lesion in the sites affected. The orbit remains an uncommon site of affectation of this relatively common disease. It is noteworthy that this is the first reported case, to the best of our knowledge, of orbital intravascular papillary endothelial hyperplasia in a Nigerian child.Case presentationThe case reported here is an orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The first theory originally proposed by Masson, states that endothelial proliferation is the primary phenomenon whereas the thrombus arises secondary to endothelial proliferation. [ 2 ] In contrast, Clearkin and Enzinger in 1976 suggested that this papillary structure appears after a preexisting thrombus organizes. Nowadays, it is considered to be a reactive vascular proliferation following traumatic vascular stasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first theory originally proposed by Masson, states that endothelial proliferation is the primary phenomenon whereas the thrombus arises secondary to endothelial proliferation. [ 2 ] In contrast, Clearkin and Enzinger in 1976 suggested that this papillary structure appears after a preexisting thrombus organizes. Nowadays, it is considered to be a reactive vascular proliferation following traumatic vascular stasis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1923, Pierre Masson first described an intravascular papillary proliferation formed within the lumen of inflamed hemorrhoidal plexus in a man and named it “Hemangioendotheliome vegetant intravasculaire.”[ 1 ] From the time of its initial description it has been referred to by various eponyms, including Masson's tumor, Masson's hemangioma, Masson's intravascular hemangioendothelioma, intravascular papillary endothelial hyperplasia (IPEH) or reactive papillary endothelial hyperplasia. [ 2 ] Masson described it to be a form of neoplasm and explained the pathogenesis as proliferation of endothelial cells into the vessel lumen, followed by obstruction and secondary degeneration and necrosis. On the other hand, Henschen[ 3 ] depicted the lesion as a reactive process rather than a neoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, angiosarcoma is rarely located intravascular, usually invading tissues outside the vessel. Solid areas and necrosis are frequent fi ndings in angiosarcomas 17 . Benign conditions such as hemangiomas, lymphangiomas, hematomas, vascular malformations, pyogenic granulomas, angiolymphoid hyperplasias with eosinophilia, fi bromas, traumatic neuromas, neurofi bromas, schwannomas should also be considered in the diff erential diagnosis of IPEH.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular papillary endothelial hyperplasia (IPEH) was first described by Pierre Masson as an intravascular papillary proliferation that forms within the lumen of an inflamed hemorrhoidal plexus, which was named vegetated intravascular hemangioendothelioma. Since then, various terms were considered for this pathology, such as hemangioendothelioma and reactive papillary endothelial hyperplasia or better known as Masson's hemangioma [1][2][3]. It can arise from normal blood vessels or in vascular malformations.…”
Section: Introductionmentioning
confidence: 99%